2021
DOI: 10.1002/asia.202001358
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cellulose Substance Based Energy Materials

Abstract: Natural cellulose substances have been proven to be ideal structural templates and scaffolds for the fabrication of artificial functional materials with designed structures, psychochemical properties and functionalities. They possess unique hierarchically porous network structures with flexible, biocompatible, and environmental characteristics, exhibiting great potentials in the preparation of energy‐related materials. This minireview summarizes natural cellulose‐based materials that are used in batteries, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 170 publications
0
10
0
Order By: Relevance
“…Due to the larger specific surface area and the mesoporous structure of the MnO 2 -TiO 2 -carbon-47.28% composite, this material could supply sufficient active sites and accelerate electron transportation during Li + insertion/extraction processes, thus leading to better electrochemical performance of the electrode material. Hence, it is concluded that the composite with a larger pore volume and higher specific surface area is able to deliver a high specific capacity and long cycling life during the charge/discharge processes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the larger specific surface area and the mesoporous structure of the MnO 2 -TiO 2 -carbon-47.28% composite, this material could supply sufficient active sites and accelerate electron transportation during Li + insertion/extraction processes, thus leading to better electrochemical performance of the electrode material. Hence, it is concluded that the composite with a larger pore volume and higher specific surface area is able to deliver a high specific capacity and long cycling life during the charge/discharge processes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natural cellulose substances, which possess unique interwoven network structures, are verified to be a desirable structural matrix and template for the self-assembly of active guest components on their surfaces through a layer-by-layer method, which shows great potential in the fabrication of cellulose-derived materials for lithium-ion batteries. The hierarchical porous structures of cellulose substance-derived functional nanomaterials are unique [ 31 ], and cannot be obtained using other synthesis method, such as the combination of different nanoscale building blocks [ 16 ]. Herein, a bio-inspired nanofibrous MnO 2 -TiO 2 -carbon composite was prepared by employing natural cellulose substances (commercial laboratory filter paper) as both the carbon source and the structural matrix using a facile sol–gel process and hydrothermal procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose and cellulose-based materials are not only earth abundant and biocompatible, but also contain intrinsic structures for transformative device performance [ 3 ]. While many innovative structures and devices as well as applications have been published and demonstrated, substantial challenges still exist in the fundamental science, and the commercialization of cellulose-based materials is a necessity in solving the emerging problems and demands [ 3 , 4 , 5 , 6 ]. The great advantage of cellulose or cellulose-based products and materials is that they can be produced from various byproducts or waste products emerging during food production such as various straws, peelings, husks, bagasse, corn stalks, or cobs, etc., or during wood processing [ 7 , 8 , 9 , 10 ].…”
Section: Introduction and Scopementioning
confidence: 99%
“…Based on biomimetic synthesis, the morphological control of functional materials is accomplished by combining chemical building blocks and natural substances with unique structures. Natural cellulose products (e.g., filter paper for quantitative analysis) possess the advantages of being abundant, environmentally friendly and biocompatible, and the functional hydroxyl groups on the surface provide a chemical environment for the deposition of the guest components [ 29 30 ]. According to our results, the composite photocatalysts synthesized by employing natural cellulose as the template had enhanced the photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%